2016
DOI: 10.1007/s12311-016-0829-2
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic Children Show Atypical Cerebellar Activation and Cerebro-Cerebellar Functional Connectivity in Orthographic and Phonological Processing

Abstract: Previous neuroimaging studies have found atypical cerebellar activation in individuals with dyslexia in either motor-related tasks or language tasks. However, studies investigating atypical cerebellar activation in individuals with dyslexia have mostly used tasks tapping phonological processing. A question that is yet unanswered is whether the cerebellum in individuals with dyslexia functions properly during orthographic processing of words, as growing evidence shows that the cerebellum is also involved in vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 69 publications
2
46
4
1
Order By: Relevance
“…31 Feng et al further explored cerebrocerebellar functional connectivity and suggested atypical connectivity patterns existed between the left cerebellum and the left fusiform gyrus during orthographic processing, whereas increased connectivity between the right cerebellum and the left supramarginal gyrus was found during phonological processing. 32 However, in the present study, the integrity of the right cerebellar tracts was significantly associated with the children's performance of character recognition. The findings were similar to research that investigated English-speaking children with DD, indicating that the right cerebellum was an anatomical area that could be used to discriminate DD with strong phonological differences from typically developing readers.…”
Section: Discussioncontrasting
confidence: 68%
“…31 Feng et al further explored cerebrocerebellar functional connectivity and suggested atypical connectivity patterns existed between the left cerebellum and the left fusiform gyrus during orthographic processing, whereas increased connectivity between the right cerebellum and the left supramarginal gyrus was found during phonological processing. 32 However, in the present study, the integrity of the right cerebellar tracts was significantly associated with the children's performance of character recognition. The findings were similar to research that investigated English-speaking children with DD, indicating that the right cerebellum was an anatomical area that could be used to discriminate DD with strong phonological differences from typically developing readers.…”
Section: Discussioncontrasting
confidence: 68%
“…In a neuroanatomical study employing diffusion tensor imaging, Travis, Leitner, Feldman, and Ben‐Shachar () found fractional anisotropy of the cerebellar peduncles in children and adolescents to be correlated with reading skills. Most relevant to the current study, in Chinese children with dyslexia, Feng et al () found differences in activity and functional connectivity in the cerebellum. However, to date there have been no studies comparing functional connectivity of the cerebellum during reading in an alphabetic language in children with and without dyslexia, although such an approach would be important to test the cerebellar deficit hypothesis of dyslexia.…”
Section: Introductionmentioning
confidence: 63%
“…It is worth noting that only six (from five studies) of the 20 original experiments included in the meta-analysis reported cerebellar activity during reading-related tasks (J. R. Booth et al, 2001;Gaillard, Balsamo, Ibrahim, Sachs, & Xu, 2003;Hoeft et al, 2006;Noble, Wolmetz, Ochs, Farah, & McCandliss, 2006;Rimrodt et al, 2009). In addition to these studies included in this meta-analysis, a study of Chinese children found cerebellar activation (bilateral crus I, right crus II) during a phonological task and cerebellar activation (bilateral crus I, right lobule VI) during an orthographic task, when contrasted with fixation (Feng et al, 2017). Interestingly, this study and all the 20 experiments included in the meta-analysis by Martin et al (2015) used a low-level comparison condition, suggesting that any cerebellar activation during reading-related task found in these studies could be due to motor-related functions of the task (e.g., eye-movements during reading or button pressing).…”
Section: Activation In Typical Readersmentioning
confidence: 99%
“…In recent years, the role of the cerebellum in processing nonmotor sequential information including linguistic information has been established (Marien & Beaton, 2014). For instance, the cerebellum plays a crucial role in infants during speech perception (Deniz Can, Richards, & Kuhl, 2013), in children and adults during tasks involving syntactic rules (Koziol et al, 2014; Pliatsikas, Johnstone, & Marinis, 2014), and in children during reading tasks (Feng et al, 2016). …”
Section: Known Sequential Processing Deficits In Dyslexiamentioning
confidence: 99%